2005
DOI: 10.1080/15287390590956551
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Modeling of the Accumulation in Plasma and Tissue Lipids of a Mixture of PCB Congeners in Female Sprague-Dawley Rats

Abstract: This study aimed to develop a physiologically based model for simulating the concentrations of polychlorinated biphenyls (PCBs) in tissue and plasma lipids of rats exposed to PCB mixtures. The model was based on the assumption that the neutral lipid fraction is the only critical determinant of the tissue distribution of PCBs, and that the solubility/retention in other tissue components is negligible. The volumes of the model compartments reflected the volumes of neutral lipids, whereas the flow rates correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…First, a question arises as to whether or not the exposure levels we used were realistic. Based on existing studies by others (51), it is safe to assume that our pups had plasma PCB levels of 50-1,000 ppb, which, although very high, is of the same order of magnitude of total PCB levels for populations near severely contaminated sites (52). Our rat pups attained such levels of contamination solely via exposure in utero and nursing.…”
Section: Discussionmentioning
confidence: 99%
“…First, a question arises as to whether or not the exposure levels we used were realistic. Based on existing studies by others (51), it is safe to assume that our pups had plasma PCB levels of 50-1,000 ppb, which, although very high, is of the same order of magnitude of total PCB levels for populations near severely contaminated sites (52). Our rat pups attained such levels of contamination solely via exposure in utero and nursing.…”
Section: Discussionmentioning
confidence: 99%
“…A blood-binding protein such as m-MUP traps the BDE-47, and thus increases the amount eliminated by glomerular filtration via the kidneys. Previous results for other highly lipophilic chemicals (Béliveau and Krishnan 2000; Emond et al 2005; Proost et al 1996; Schoenborn 1976) indicated that the actual BDE-47 blood concentration should be lower than what was observed by Staskal et al (2005) and Sanders et al (2006a) if lipophilicity is the only parameter responsible for the distribution of BDE-47. This observation supports protein binding to BDE-47 by itself; therefore, the observation was instrumental in driving the selection of this description.…”
Section: Discussionmentioning
confidence: 88%
“…In the case of HLVOCs, one critical determinant relates to solubility in the neutral lipid component of tissues and blood. Several authors, recognizing the critical role of lipids in determining the tissue distribution of superlipophilic compounds, Toxicology Mechanisms and Methods Downloaded from informahealthcare.com by CDL-UC Davis on 11/04/14 402 C. EMOND AND K. KRISHNAN have attempted to develop PBPK models based on tissue lipid contents (Lindstrom et al 1976;Pelekis et al 1995;van der Molen et al 1996;Levitt 2002;Emond et al 2005). The present study has, for the first time, shown that a physiological pharmacokinetic model based on neutral lipid content of tissues and blood does not require the use or estimation of tissue:blood partition coefficients and still enables adequate simulation of the uptake and disposition of HLVOCs (e.g.,and 1,2, in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The solubility of highly lipophilic substances in polar lipids and water fractions of the various compartments is negligible and is explained by the relatively high n-octanol:water partition coefficients of such chemicals. Therefore, the kinetics of highly lipophilic chemicals can be simulated solely with the consideration of their solubility and distribution in neutral lipid fractions of tissues and blood (Lindstrom et al 1976;van der Molen et al 1996;Levitt 2002;Emond et al 2005). Consequently, if the volumes of the model compartments represented only the neutral lipid fraction of 396 C. EMOND AND K. KRISHNAN tissues and blood, then there is no necessity to use or estimate a tissue:blood partition coefficient since the (tissue) neutral lipid: (blood) neutral lipid partition coefficient should be unity.…”
Section: Introductionmentioning
confidence: 99%